Suppressive Activity of Vitamin D3 on Matrix Metalloproteinase Production From Cholesteatoma Keratinocytes In Vitro - Hitome Kobayashi; Kazuhito Asano; Ken-ichi Kanai; Harumi Suzaki (Hindawi Limited, 2005)
There is much evidence that degradation of the extracellular matrix is essential for the development of cholesteatomas and that this is induced by activation of matrix metalloproteinases (MMPs). Vitamin D3 (VD3) has several well-recognised biological activities, including suppression of MMP production. The present study, therefore, was undertaken to examine whether VD3 could suppress MMP production from cholesteatoma keratinocytes in vitro. Keratinocytes (2.5×105 cells/mL) induced from cholesteatoma tissue specimens were cultured with various concentrations of VD3. After one hour, lipopolysaccharide was added to the cell cultures at 100 μg/mL. The culture supernatants were then collected and assayed for MMP-1 and MMP-3 by ELISA. We also used ELISA to measure the levels of both TIMP (tissue inhibitor of metalloproteinase)-1 and TIMP-2 in culture supernatants. Addition of VD3 into keratinocyte cultures caused the suppression of MMP and TIMP production, which was increased by LPS stimulation. This was dose-dependent. The present results showing the suppressive activity of VD3 on the production of MMPs, which are responsible for tissue remodeling, strongly suggest that VD3 would be a good candidate for an agent in the medical treatment of, or prophylaxis for, cholesteatomas.